Pochlebstwo - nadużycie języka i trucizna wzajemnych relacji. Perspektywa średniowieczna = Flattery - the abuse of language and the poison of mutual relationships. Medieval perspective - Królikowski, Janusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Flattery (from Latin: adulatio), especially in the Middle Ages, was the subject of multiple and insightful analyses, which, despite certain differences in its understanding, unanimously perceived it as a serious moral transgression, destroying interpersonal relationships. Under the influence of these ideas, Dante in "The Divine Comedy" modified the traditional doctrine of the seven cardinal vices, including flattery among them and proposing severe punishments for sinners who used it.
Keywords: pochlebstwo; kłamstwo; zwodzenie; fałsz; spryt; zmienność; trucizna duchowa; flattery; lie; deception; falsehood; cunning; volatility; spiritual poison